Vaccination of Children with Hemoblastosis - M. P. Коstinov; A. A. Таrasova (Эпидемиология и вакцинопрофилактика, 2018)
Recommendations highlighted features vaccination children with hemoblastosis. It is shown how the immunization scheme may be changed according to the pathology and the age of the child.